2019
DOI: 10.1186/s12879-019-4512-3
|View full text |Cite
|
Sign up to set email alerts
|

A multiplex PCR assay for the simultaneous detection of Taenia hydatigena, T. multiceps, T. pisiformis, and Dipylidium caninum infections

Abstract: Background Taenia hydatigena, T. multiceps, T. pisiformis, and Dipylidium caninum are four common large and medium-sized tapeworms parasitizing the small intestine of dogs and other canids. These parasites cause serious impact on the health and development of livestock. However, there are, so far, no commercially available molecular diagnostic kits capable of simultaneously detecting all four parasites in dogs. The aim of the study was therefore to develop a multiplex PCR assay that will accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…These may be due to no health control measures and their habits exposed to natural infection more than owned dogs. The prevalence rate (32.54%) by molecular method (PCR), these agreed with (Zhu et al, 2019), who showed that no cross-reactivity was observed with other tapeworms inhabiting the small intestine as well as with each other. The minimum detected DNA ranged from 0.1 to 1 ng, low enough to produce results in case of low DNA yield (Mirbadie et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These may be due to no health control measures and their habits exposed to natural infection more than owned dogs. The prevalence rate (32.54%) by molecular method (PCR), these agreed with (Zhu et al, 2019), who showed that no cross-reactivity was observed with other tapeworms inhabiting the small intestine as well as with each other. The minimum detected DNA ranged from 0.1 to 1 ng, low enough to produce results in case of low DNA yield (Mirbadie et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…It is responsible for major medical and economic losses in animals (Ulziijargala et al, 2020), due to widespread parasite that can infect a wide range of herbivorous animals with its larval stage, Cysticercus tenuicollis (Myczkaa et al, 2019;AbouLaila et al, 2020). Furthermore, adult worms parasitize mostly present in small intestine of canids and produce eggs, which are infective to intermediate hosts (Mirbadie et al, 2019;Zhu et al, 2019). Taeniid tapeworms associated with the sheepdog life cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transmission of this parasite is sustained by the predator-prey relationship of the definitive and intermediate hosts. T. pisiformis infections often cause much more severe damage in intermediate hosts than in definitive hosts, where infections are mostly subclinical [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Dot-ELISA diagnostic method has been reported for detection of C. pisiformis, but has high false positive rate limit applicability [9]. Multiplex PCR has been studied as a diagnostic method for T. pisiformis in dog feces, but cannot be used for the diagnosis of rabbit cysticercosis [10]. Thus, there is an urgent need to develop a new method for early diagnosis for rabbit in order to reduce the losses due to cysticercosis.…”
Section: Introductionmentioning
confidence: 99%